2015
DOI: 10.15604/ejef.2015.03.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Efficiency of Vat in Eu Member States

Abstract: Value added tax (VAT) in the countries of European Union is one of the most important sources of tax revenues. During the recent financial crisis, the importance of this tax has increased significantly. Despite of the fact that VAT is the best harmonized tax in the EU, the construction of VAT in member states may significantly differ. The differences may relate to issues such as the number and the level of applicable tax rates and the range of goods and services covered by the preferential VAT rates. The aim o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…VAT eff ectiveness may be aff ected by either a policy gap or a non-compliance gap (Adamczyk 2015), so there are two possibilities, both of which should attract the immediate attention of the policymakers: severe country dependence on imported products (which is the policy gap and a sustainability issue) or domestic tax fraud (which is the non-compliance gap and an administrative issue). Th e same is essentially correct for Russia, which experienced a signifi cant decrease in VAT collection on domestic transactions in 2005 -2008, though a dependence of Russia on import is less crucial.…”
Section: Policy Lessonsmentioning
confidence: 99%
See 1 more Smart Citation
“…VAT eff ectiveness may be aff ected by either a policy gap or a non-compliance gap (Adamczyk 2015), so there are two possibilities, both of which should attract the immediate attention of the policymakers: severe country dependence on imported products (which is the policy gap and a sustainability issue) or domestic tax fraud (which is the non-compliance gap and an administrative issue). Th e same is essentially correct for Russia, which experienced a signifi cant decrease in VAT collection on domestic transactions in 2005 -2008, though a dependence of Russia on import is less crucial.…”
Section: Policy Lessonsmentioning
confidence: 99%
“…However, the literature analysis showed that the comparative analysis across regions or countries usually covers legal developments in tax pronouncements and the comparison of tax revenues (Tanzi et al 2008;Petersen 2010) or the eff ect of taxation on FDI or other factors of production (Strasky and Pashinova 2012;Tyutyuryukov 2015b). Adamczyk (2015) is a rare example of estimating VAT eff ectiveness (based on VAT Revenue Ratio), in particular showing exchangeability between the noncompliance gap and the policy gap and the negative impact of tax preferences and the general eff ectiveness of VAT in EU.…”
Section: Introductionmentioning
confidence: 99%
“…Value added tax has become the most common consumption tax in the world (Giesecke and Tran, 2012), and Keen (2013) indicates that VAT is adopted in more than 150 countries in the world, where the share of VAT revenues amounts to more than 20% of the global tax revenues. During the financial crisis of 2008, the importance of value added tax increased significantly (Adamczyk, 2015). Aizenman and Jinjarak (2008) point out that VAT is tax collected throughout the production chain.…”
Section: Introductionmentioning
confidence: 99%